(untitled) - Michaels, John G. (New York, 1992)
This book presents a wide variety of interesting applications of discrete mathematics in a flexible and accessible format. They are arranged in three sections: discrete structures and computing; combinatorics,; and graph theory
Keywords: Algebra, abstract,Combinatorial analysis,Logic, symbolic and mathematical; Oulines, syllabi, etc,Oulines, syllabi, etc,Oulines, syllabi, etc